Proteolytic α‐synuclein cleavage in health and disease - Bluhm, Alexandra; Schrempel, Sarah; von Hörsten, Stephan; Schulze, Anja; Roßner, Steffen (International Journal of Molecular Sciences, 2021)
In Parkinson’s disease, aggregates of α‐synuclein within Lewy bodies and Lewy neurites represent neuropathological hallmarks. However, the cellular and molecular mechanisms triggering oligomeric and fibrillary α‐synuclein aggregation are not fully understood. Recent evidence indicates that oxidative stress induced by metal ions and post‐translational modifications such as phosphorylation, ubiquitination, nitration, glycation, and SUMOylation affect α‐synuclein conformation along with its aggregation propensity and neurotoxic profiles. In addition, proteolytic cleavage of α‐synuclein by specific proteases results in the formation of a broad spectrum of fragments with consecutively altered and not fully understood physiological and/or pathological properties. In the present review, we summarize the current knowledge on proteolytical α‐ synuclein cleavage by neurosin, calpain‐1, cathepsin D, and matrix metalloproteinase‐3 in health and disease. We also shed light on the contribution of the same enzymes to proteolytical processing of pathogenic proteins in Alzheimer’s disease and report potential cross‐disease mechanisms of pathogenic protein aggregation.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Animal models; Dementia with Lewy bodies; Parkinson’s disease; Post‐translational modification; Proteolysis; Substantia nigra; α‐synuclein